Diagnostic Analysis of Students’ Hydrocarbon Concept Mastery Using Two-Tier Multiple Choice Test - Mislawati Mislawati; Isna Rezkia Lukman; Ade Masyithah; Mifla Hayatul; Mas Mudah Nazwa; Halimatus Sakdiah (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze learning difficulties in relation to students' levels of conceptual understanding—categorized as conceptually understood, misconceptions, and lack of understanding—among 11th-grade science students (Grade XI MIPA) in the Teupah Barat District, specifically concerning the topic of hydrocarbons. A Two-Tier Multiple Choice diagnostic test was employed as the primary instrument. The study utilized a qualitative descriptive method. The population comprised all Grade XI MIPA students from senior high schools in the Teupah Barat District. The sample included 40 students from SMA Negeri 1 Teupah Barat and SMA Negeri 2 Teupah Barat, selected using purposive sampling techniques. Data analysis was conducted using descriptive statistics to process and interpret the students' responses. The results indicate that the Two-Tier Multiple Choice diagnostic test was effective in identifying students' conceptual understanding and in uncovering alternative conceptions through dominant incorrect answer choices that diverged from scientifically accurate concepts.The findings reveal that among the participants, 64% demonstrated conceptual understanding, 23% exhibited misconceptions, and 13% showed a lack of understanding regarding the topic of hydrocarbons. These results highlight the diagnostic tool's utility in pinpointing areas where conceptual reinforcement is necessary to enhance students’ comprehension in chemistry education.